Assessment of Factors Associated with Mandibular Anterior Crowding in Mixed Dentition - Vikranth Omprakash Shetty; M. S. Ravi; Shraddha Shetti; Jayashri Bhangare; Varada Kudalkar; Shruti Dhanshetti (Wolters Kluwer Medknow Publications, 2024)
Introduction: Dental crowding can be defined as a disparity in the relationship between the tooth size and arch length, which results in imbrication and rotation of teeth. Crowding of permanent teeth, especially in the anterior part of the mandible, is believed to be the most frequent form of malocclusion in children. The appropriate age for treatment of crowding is the late mixed dentition period. Aim: To assess and compare the dental and skeletal factors associated with early crowding and non-crowding in children with mixed dentition. Methodology: This experimental cross-sectional study was conducted in Mangalore within 24 months. A total of sixty subjects between the age group of 7-10 years of both sexes were included in the study, in which the experimental group includes 30 subjects with mandibular crowding and the control group includes 30 subjects without lower anterior crowding. A comparison of model analysis parameters between the crowding group and the non-crowding group was done using Student's t-test. Any P-value of ≤0.05 is considered statistically significant. Results: The result showed that dental parameters like total incisor width were greater and intercanine width was found to be reduced in the crowding group, whereas arch diameter was found to be increased in non-crowding group, which was statically significant (P-value). Skeletal parameters like SNA and SNB were found to be significantly decreased in crowding individuals (P-values of 0.011 and 0.04, respectively). Conclusion: The total incisor width was found to be greater in the crowding group when compared to the non-crowding group, and this could be one of the reasons for the cause of crowding in the early mixed dentition period. The intercanine width and arch diameter were reduced in the crowding group when compared to the non-crowding group. Crowding in the permanent dentition may either be eliminated or at least severity can be reduced if interceptive orthodontics is initiated at an early stage in such children.